The Progress in the Treatment of Hepatocellular Carcinoma With Portal Vein Tumor Thrombus - Luo, Fangzhou; Li, Mengxia; Ding, Jun; Zheng, Shusen (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of most prevalent cancer and is a serious healthcare issure worldwide. Portal vein tumor thrombus (PVTT) is a frequent complication and remains as the blockage in the treatment of HCC with high recurrence rate and poor prognosis. There is still no global consensus or standard guideline on the management of HCC with PVTT. In western countries, Sorafenib and Lenvatinib are recommended as the first-line treatment options for HCC patients with PVTT where this condition is now regarded as BCLC Stage C regardless of PVTT types. However, there is growing evidence that supports the close relationship of the extent of PVTT to the prognosis of HCC. Besides the targeted therapy, more aggressive treatment modalities have been proposed and practiced in the clinic which may improve the prognosis of HCC patients with PVTT and prolong the patients’ survival time, such as transarterial chemoembolization, radiotherapy, hepatic resection, liver transplantation, and various combination therapies. Herein, we aim to review and summarize the advances in the treatment of HCC with PVTT.